Cash Waqf Integrated with Syariah-Based Koperasi Merah Putih: : An Innovative Model for Rural Economic Empowerment - Luthfi Rantaprasaja; Noviendri Djalil; Aan Kurnia (Jurnal Manajemen, 2026)
This article explores the integration of Islamic cash waqf as a governance and financing mechanism within Syariah-based cooperatives as a response to the Indonesian government’s initiative to establish Koperasi Merah Putih (KMP) in the rural areas. Although the initiative represents a positive movement towards community-based economic development, it also raises the concern of possible state or corporate capture that could destroy the cooperative’s grassroots character. Utilizing a qualitative-descriptive and conceptual approach, the research synthesizes policy papers, cooperative governance frameworks, and Islamic social finance to create a normative model for trust-based financial management. The model proposes waqf as a trust fund mechanism to dissociate public financing (APBN, CSR, Dana Desa) from capital contributed by members, thus enabling business financing through Islamic contracts such as qardhul hasan, musyarakah, and mudharabah muqayyadah. The findings indicate the integrated model enhances transparency, sustains communal ownership and governance, increases cooperative autonomy, and upholds the maqashid sharia. The study illustrates the ethical approach of using waqf and other Islamic financial tools to aid the modernization of rural development while preserving local agency